Prognostic humility and ethical dilemmas after severe brain injury: Summary, recommendations, and qualitative analysis of Curing Coma Campaign virtual event proceedings - Kreitzer, Natalie; Murtaugh, Brooke; Creutzfeldt, Claire; Fins, Joseph J.; Manley, Geoff; Sarwal, Aarti; Dangayach, Neha (Frontiers in Human Neuroscience, 2023)
Background: Patients with severe acute brain injuries (SABI) are at risk of living with long-term disability, medical complications, and high rates of mortality. Determining an individual patient’s prognosis and conveying this to families can be challenging. We conducted a webinar as part of the Curing Coma Campaign which discussed topics focused on prognostic uncertainty, communicating prognosis to family members, gaps within healthcare systems, and research infrastructure related to patients experiencing SABI. Methods: A multidisciplinary group of experts were invited as speakers and moderators of the webinar, “Prognostic Humility and Ethical Dilemmas in Acute Brain Injury.” The content was transcribed verbatim. Two authors read the transcription, developed a code book, and independently coded the transcript using inductive thematic analysis. Results: Two main themes were discussed: 1) the concept of prognostic uncertainty in the acute setting, and 2) lack of access to and evidence for rehabilitation specialized continuum of care efforts specific to SABI research. Within these two main themes, there were 5 sub-themes, broken down into 23 unique codes. We identified several strategies for speaking with surrogates of patients with SABI. We identified gaps in the United States health system and in research to improve the care of patients with SABI. Conclusions: Authors identified and analyzed themes related to prognostic uncertainty with SABI. Recommendations were outlined for clinicians who engage with surrogates of SABI patients to foster informed decisions. Recommendations for changes in healthcare systems and research support are provided to continue to propel SABI science forward to improve prognostic certainty.